2022
DOI: 10.1097/mca.0000000000001168
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with recurrent spontaneous coronary artery dissection: a systematic review and meta-analysis

Abstract: BackgroundThe risk of recurrent spontaneous coronary artery dissection (SCAD) is a major concern to SCAD patients and clinicians. Identifying the high-risk subsets of recurrent SCAD remains an ongoing challenge. The meta-analysis aimed to assess the potential predictors for SCAD recurrence. Methods A literature search was performed in PubMed to collect studies that assessed potential factors associated with recurrence of SCAD among angiographically confirmed SCAD patients, including pregnancy, ventricular arrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Investigating the reasons behind this and finding susceptible patients is of utmost importance to reduce the associated morbidity and mortality and prevent unnecessary interventions and hospitalizations. In a meta-analysis by Gerald et al [138], hypertension and FMD were major stressors for recurrence. In our series, stress-related SCAD recurrences were associated with neither arterial hypertension nor FMD.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating the reasons behind this and finding susceptible patients is of utmost importance to reduce the associated morbidity and mortality and prevent unnecessary interventions and hospitalizations. In a meta-analysis by Gerald et al [138], hypertension and FMD were major stressors for recurrence. In our series, stress-related SCAD recurrences were associated with neither arterial hypertension nor FMD.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, most of these women managed pregnancy and lactation without any evidence of an increased risk of SCAD recurrence compared to women with a history of SCAD who did not become pregnant (44). Furthermore, in a meta-analysis involving 4,206 SCAD patients, pregnancy did not exhibit a significant association with recurrent SCAD (45).…”
Section: Hormonal Influences and Scadmentioning
confidence: 97%
“… 56 A meta-analysis of 14 studies, comprised of 4206 patients, examining factors associated with recurrence of SCAD, showed that hypertension (risk ratio [RR] 1.49) and FMD (RR 2.02) conferred a greater risk. 57 By contrast, the use of beta-blockers (RR 0.51) was associated with a reduced risk of SCAD recurrence. In the recently published 3-year outcomes of the Canadian SCAD Cohort Study, recurrent de novo SCAD was seen in 2.4% of patients, and recurrent MI was seen in 5.7%.…”
Section: What Is New In the Long-term Management Of Scad?mentioning
confidence: 99%